2015
DOI: 10.1016/j.celrep.2015.10.056
|View full text |Cite
|
Sign up to set email alerts
|

ADF and Cofilin1 Control Actin Stress Fibers, Nuclear Integrity, and Cell Survival

Abstract: SummaryGenetic co-depletion of the actin-severing proteins ADF and CFL1 triggers catastrophic loss of adult homeostasis in multiple tissues. There is impaired cell-cell adhesion in skin keratinocytes with dysregulation of E-cadherin, hyperproliferation of differentiated cells, and ultimately apoptosis. Mechanistically, the primary consequence of depleting both ADF and CFL1 is uncontrolled accumulation of contractile actin stress fibers associated with enlarged focal adhesions at the plasma membrane, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 52 publications
(62 reference statements)
5
75
1
Order By: Relevance
“…The effects are less prominent when ADF is depleted alone and are most severe after co-depletion of both ADF and CFL1, implying functional redundancy in this cellular context (Hotulainen et al, 2005;Wiggan et al, 2012). Increased contractility following ADF and CFL1 co-depletion has also recently been reported, where it was shown that a similar mechanism involving tight control of contractile actin fibres by cofilins regulates nuclear architecture and ultimately cell viability (see below) (Kanellos et al, 2015). Interestingly, another consequence of dysregulation of the actin cytoskeleton occurs during neuritogenesis.…”
Section: New and Emerging Roles Of Cofilins Contractilitymentioning
confidence: 87%
See 4 more Smart Citations
“…The effects are less prominent when ADF is depleted alone and are most severe after co-depletion of both ADF and CFL1, implying functional redundancy in this cellular context (Hotulainen et al, 2005;Wiggan et al, 2012). Increased contractility following ADF and CFL1 co-depletion has also recently been reported, where it was shown that a similar mechanism involving tight control of contractile actin fibres by cofilins regulates nuclear architecture and ultimately cell viability (see below) (Kanellos et al, 2015). Interestingly, another consequence of dysregulation of the actin cytoskeleton occurs during neuritogenesis.…”
Section: New and Emerging Roles Of Cofilins Contractilitymentioning
confidence: 87%
“…Moreover, double depletion of ADF and CFL1 (but not single deletion) in the skin epithelium of adult mice also leads to loss of tissue homeostasis, with extensive epidermal thickening, aberrant cell morphology with loss of cell-cell contacts, hyperproliferation and a pronounced accumulation of filamentous actin (Kanellos et al, 2015), indicating that there is some functional redundancy between ADF and CFL1 in some tissue contexts.…”
Section: Box 1 Physiological Importance Of Adf and Cofilinsmentioning
confidence: 99%
See 3 more Smart Citations